2021
DOI: 10.55340/e2j.v7i2.692
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Students’ Motivation in Reading English

Abstract: The problem in this research was how is students’ motivation in reading English at grade VIII SMP Negeri 4 Baubau. This research was descriptive qualitative research. The population of the research was grade VIII of SMP Negeri 4 Baubau which consisted of 11 classes with total 345 students. The sample in this research was taken with random sampling technique that was class VIII.1 which consisted of 25 students. The instrument used was Motivations for Reading Questionnaire (MRQ). The research outcome showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The result of this study showed that students can develop reading ability because they have average level of intrinsic motivation. This statement is also supported by (Maneba et al, 2021) who found that there are five students who are in the high motivation category, 13 out of the total students' motivation in reading English text is at an average level, and seven students out of all total students are in low motivation level.…”
Section: Discussionmentioning
confidence: 58%
“…The result of this study showed that students can develop reading ability because they have average level of intrinsic motivation. This statement is also supported by (Maneba et al, 2021) who found that there are five students who are in the high motivation category, 13 out of the total students' motivation in reading English text is at an average level, and seven students out of all total students are in low motivation level.…”
Section: Discussionmentioning
confidence: 58%
“…By fostering a positive reading culture, not only are students better equipped for academic challenges, but they also develop valuable skills that extend beyond the classroom. A love for reading instilled during high school can shape individuals into lifelong learners, fostering intellectual curiosity, critical thinking, and a deeper understanding of the world around them (Maneba et al, 2021). Thus, these efforts not only benefit the academic journey but also lay the foundation for a fulfilling and enriching life marked by a continuous pursuit of knowledge and personal growth.…”
Section: Discussionmentioning
confidence: 99%